The Effectiveness of Digital Virtual Reality-Based Therapy in Reducing Anxiety Among Patients Undergoing Gastrointestinal Endoscopy - Bayu Aji Sismanto; Dewi Gayatri; Dhea Natashia; Wati Jumaiyah; Winda Yuniarsih (Jurnal Ners, 2025)
Psychological responses such as anxiety often arise from negative perceptions in situations perceived as threatening, even when they should not induce fear. These anxiety-induced responses can lead to increased hemodynamic parameters such as elevated blood pressure, heart rate, and respiratory rate—particularly prior to medical procedures. This study aimed to evaluate the effectiveness of a digital virtual reality (VR)-based therapeutic intervention in reducing patient anxiety before undergoing gastrointestinal endoscopy. A quasi-experimental design was employed, involving both an experimental group and a control group using a pretest-posttest control group approach. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI). The intervention consisted of a 6-minute immersive VR video featuring calming mountain and beach scenery. A total of 50 respondents participated, with 25 in each group. Data were analyzed using paired and independent t-tests. Results showed no statistically significant difference in mean anxiety scores between the intervention and control groups (MD = 0.23, df = 48, t = 0.59, 95% CI: -0.56 to 1.03, p > 0.001). These findings suggest that the digital VR-based therapy was not statistically effective in reducing pre-endoscopy anxiety. Future interventions may require more immersive and interactive VR experiences—such as 360-degree simulations of endoscopic procedures—to achieve more substantial effects.